Penggunaan Media Alamiah Mata Pelajaran IPA Kelas 4 - Fitriani, Agustina Laelatul (Educreative : Jurnal Pendidikan Kreativitas Anak, 2020)
Understanding of the material in science subjects class 4 at MIMA Karangpucung is currently only theoretical and only sees pictures. Therefore students are not easy to understand the learning of the theory. So that student learning outcomes decline or are not satisfactory. So it requires the use of natural media that can be found in the environment around Madrasas. The goal is to be able to revive the spirit of students in the process of learning Natural Sciences. The results of the study are expected for the teacher to be able to develop knowledge and skills and arouse self-confidence so that they will always be excited and eager to improve their learning. For students to improve understanding in absorbing the material being studied so that the learning process and outcomes will be further improved. For schools it is useful to assist schools in creating quality educational institutions that will become a model or model for schools, teachers who are professionally experienced and are trusted by parents, the community and the government